Quantifying evaporation and transpiration in field lysimeters using the soil water balance - Ukoh Haka, Imoh Bassey (University of the Free State, 2010)
The main aim of this study was to determine the transpiration efficiency coefficient (TEC) for three C3 crops; canola, wheat and lucerne. TEC relates to the efficiency of water management in crop production. It is defined as the ratio of seed or biomass to the product of transpiration and vapour pressure deficit. Of these variables, transpiration is the most difficult to measure. Two experiments (canola, 2007 and wheat, 2007&2008) were therefore designed with the aim of partitioning evapotranspiration (ET) into its components of evaporation (E) from the soil and transpiration (T) from the plant. These experiments were based on a split plot design, with two soils (Clovelly and Bainsvlei) and two surface treatments which comprised of a bare soil for measuring ET and a 50 mm thick gravel mulch for measuring T using the lysimeter unit of the University of the Free State at Kenilworth near Bloemfontein. These components were measured regularly and E was derived by subtracting T from ET. The results showed that for canola, E was 12% of the total ET (809 mm) and for wheat E was 27% of total ET (639 mm). The percentage contribution of T to ET was high in both crops: 718 mm or 88% of total ET of canola and 489 mm or 63% of total ET of wheat. Conclusive evidence showed that crops should be managed differently with respect to their individual irrigation water demands. The remaining three experiments were dedicated to factors influencing the TEC of crops. Specific objectives were to establish the effect of growth periods during the reproductive stage on the TEC of canola, the effect of weather on the TEC of wheat and effect of cutting periods on the TEC of lucerne. All experiments were conducted in the lysimeter unit and measurements were based on the soil water balance of both soils. TEC was expressed as grain yield (GY) or seed yield (SY), above-ground biomass (AGB) and total biomass (TB). Soils had no significant effect on TEC. However, TEC of canola was significantly affected by growth periods. For growth periods, TECABG varied between 3.82 and 4.95 g kPa mm-1 and TECTB between 3.94 and 5.04 g kPa mm-1. For wheat it was concluded that weather had no influence on the TEC based on AGB, but TEC based on GY was significantly lower in 2008 (TEC = 0.9 g kPa mm-1) compared to 2007 (TEC = 2.3 g kPa mm-1). This was caused by severe frost which occurred in the early reproductive stage. The result revealed a mean TECAGB of 4.75 g kPa mm-1 for the two wheat seasons. The results on lucerne suggested that cutting periods do played a significant role in the TECAGB of the crop. TEC decreased from 3.86 g kPa mm-1 for the first cutting period to 2.22 g kPa mm-1 for the sixth cutting period, with a mean TEC value of 2.84 g kPa mm-1 for all six cutting periods. TEC values for canola, wheat and lucerne in this study are consistent with values reported for other C3 crops in the semiarid environments and are therefore recommended for use in models.
Thesis (Ph.D. (Soil, Crop and Climate Sciences))--University of the Free State, 2010
Keywords: Crops and soils; Plant-soil relationships; Evapotranspiration; Vapor pressure; Soil moisture Measurement; Evaporation; Crops; Plants Transpiration; Water requirements; Transpiration